2012
DOI: 10.1128/aac.00061-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rifaximin Vaginal Tablets in Treatment of Bacterial Vaginosis: a Molecular Characterization of the Vaginal Microbiota

Abstract: ABSTRACTBacterial vaginosis (BV) is a common vaginal disorder characterized by an alteration of the vaginal bacterial morphotypes, associated with sexually transmitted infections and adverse pregnancy outcomes. The purpose of the present study was to evaluate the impact of different doses of rifaximin vaginal tablets (100 mg/day for 5 days, 25 mg/day for 5 days, and 100 mg/day for 2 days) on the vaginal microbiota of 102 European patients with BV enrolled in a multicenter, doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…The major differences from ineffective treatment were induced by 25 mg of rifaximin for 5 days, in agreement with the findings of Cruciani et al (12), who described this dosage as the best treatment regimen in terms of restoration of a healthy-like microbiota.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The major differences from ineffective treatment were induced by 25 mg of rifaximin for 5 days, in agreement with the findings of Cruciani et al (12), who described this dosage as the best treatment regimen in terms of restoration of a healthy-like microbiota.…”
Section: Discussionsupporting
confidence: 80%
“…Demographic characteristics and sexual habits of these patients are reported in Table 1. The patients had previously been enrolled in a multicenter, double-blind, randomized, placebo-controlled study (EudraCT;2009-011826-32) performed to compare the efficacy of rifaximin vaginal tablets to that of the placebo for the treatment of BV (11,12). Diagnosis of BV was made using both Amsel's criteria and Nugent score at the screening visit (V1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total bacterial DNA was extracted from vaginal rinsings by using a DNeasy blood and tissue kit (Qiagen) as previously described (18).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the clinical parameters (17), the molecular composition of vaginal communities (18), and the proteomic and metabolic profiles of vaginal fluids (19,20) revealed that treatment with 25 mg of rifaximin for 5 days can effectively counteract the alterations associated with the BV condition.…”
mentioning
confidence: 99%